Cultivating a culture of inclusivity in heliophysics - Halford, Alexa J.; Burrell, Angeline G.; Liemohn, Michael W.; Jones, McArthur; Maute, Astrid; Pulkkinen, Tuija I.; Bard, Christopher M.; McGranaghan, Ryan M.; Wilson, Lynn B.; Allen, Robert C.; Dong, Chuanfei; Vines, Sarah K.; et al. (Frontiers in Physics, 2023)
A large number of heliophysicists from across career levels, institution types, and job titles came together to support a poster at Heliophysics 2050 and the position papers for the 2024 Heliophysics decadal survey titled "Cultivating a culture of inclusivity in Heliophysics," "The Importance of Policies: It's not just a pipeline problem," and "Mentorship within Heliophysics." While writing these position papers, the number of people who privately shared disturbing stories and experiences of bullying and harassment was shocking. The number of people who privately expressed how burned out they were was staggering. The number of people who privately spoke about how they considered leaving the field for their and their family's health was astounding. And for as much good there is in our community, it is still a toxic environment for many. If we fail to do something now, our field will continue to suffer. While acknowledging the ongoing growth that we as individuals must work toward, we call on our colleagues to join us in working on organizational, group, and personal levels toward a truly inclusive culture, for the wellbeing of our colleagues and the success of our field. This work includes policies, processes, and commitments to promote: accountability for bad actors; financial security through removing the constant anxiety about funding; prioritization of mental health and community through removing constant deadlines and constant last-minute requests; a collaborative culture rather than a hyper-competitive one; and a community where people can thrive as whole persons and do not have to give up a healthy or well-rounded life to succeed.